2001
DOI: 10.1103/physrevlett.86.1027
|View full text |Cite|
|
Sign up to set email alerts
|

Attraction between Nanoparticles Induced by End-Grafted Homopolymers in Good Solvent

Abstract: The interactions between nanoparticles coated by end-grafted homopolymers of comparable size are studied using Edwards' self-consistent field (SCF) theory. The equilibrium monomer density distribution is obtained by solving the SCF equations in bispherical coordinates. It is shown that, because of the spherical geometry and redistribution of monomer density, end-grafted homopolymers in good solvent environment can induce attractive interactions. This result suggests that steric stabilization of nanoparticles r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…The addition of nanoparticles (NPs) to polymeric materials has been the subject of numerous research efforts aimed at enhancing the conductivity, gas permeability, and optical or mechanical properties of the base polymer. While such property enhancements normally require uniform NP dispersion in the polymer, most NP/polymer mixtures suffer from deleterious phase separation (leading to NP agglomeration). , One reliable pathway to obviate phase separation and to ensure good NP dispersion is to chemically graft polymer chains to the NP surface to create grafted nanoparticles (GNPs). , These GNPs have recently garnered attention for creating highly permeable mixed matrix membranes . Our previous work has demonstrated that these constructs exhibit elevated gas diffusion, tunable through variations in the grafted chain molecular weight, M n , and the grafting density, σ.…”
mentioning
confidence: 99%
“…The addition of nanoparticles (NPs) to polymeric materials has been the subject of numerous research efforts aimed at enhancing the conductivity, gas permeability, and optical or mechanical properties of the base polymer. While such property enhancements normally require uniform NP dispersion in the polymer, most NP/polymer mixtures suffer from deleterious phase separation (leading to NP agglomeration). , One reliable pathway to obviate phase separation and to ensure good NP dispersion is to chemically graft polymer chains to the NP surface to create grafted nanoparticles (GNPs). , These GNPs have recently garnered attention for creating highly permeable mixed matrix membranes . Our previous work has demonstrated that these constructs exhibit elevated gas diffusion, tunable through variations in the grafted chain molecular weight, M n , and the grafting density, σ.…”
mentioning
confidence: 99%
“…Of course, this approximation breaks down in the case of small nanocrystals and more involved approaches, such as self‐consistent field theory, have to be employed . This study shows that the interaction induced by the surfactant chain is always repulsive, in contrast with previous claims using similar simulation techniques . Moreover, when two particles approach, an important interpenetration of the ligand chains occurs before the repulsion becomes significant.…”
Section: Forces Between Nanocrystalsmentioning
confidence: 72%
“…[72] This study shows that the interaction induced by the surfactant chain is alwaysr epulsive, in contrastw ith previous claims using similar simulation techniques. [73,74] Moreover, when two particles approach, an important interpenetration of the ligand chains occurs before the repulsion becomes significant. Finally,t hese simulations explore the extent to which the Derjaguin approximationa nd its modified version can be applied.…”
Section: Surfactant Monolayer Interactionmentioning
confidence: 99%
“…Peptides adsorbed to the quantum dot surface can also have a similar stabilizing effect [133]. Conversely, it has been theoretically predicted that homopolymers, if end-grafted to nanoparticles in good solvents, may lead to nanoparticle attraction [134].…”
Section: Colloidal Stabilitymentioning
confidence: 99%